2013
DOI: 10.1007/s13592-012-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable reference genes for the measurement of transcript abundance during larval caste development in the honeybee

Abstract: -Many genes are differentially regulated by caste development in the honeybee. Identifying and understanding these differences is key to discovering the mechanisms underlying this process. To identify these gene expression differences requires robust methods to measure transcript abundance. RT-qPCR is currently the gold standard to measure gene expression, but requires stable reference genes to compare gene expression changes. Such reference genes have not been established for honeybee caste development. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…One solution is to search for suitable reference genes to normalize quantitative PCR results until specific reference genes for an experimental paradigm have been identified (Cameron et al, 2013;Reim et al, 2013). However, large sets of candidate genes may have to be studied without a priori information, particularly in two-factorial experimental designs that cross developmental stages (Cameron et al, 2013), such as ours. To reduce normalization bias, multiple reference genes can be combined (Lourenco et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One solution is to search for suitable reference genes to normalize quantitative PCR results until specific reference genes for an experimental paradigm have been identified (Cameron et al, 2013;Reim et al, 2013). However, large sets of candidate genes may have to be studied without a priori information, particularly in two-factorial experimental designs that cross developmental stages (Cameron et al, 2013), such as ours. To reduce normalization bias, multiple reference genes can be combined (Lourenco et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, raw C t values of all honey bee transcripts were more correlated with each other than ∆C t values. Therefore, we preferentially present and discuss the relative differences of immune genes but recommend a wider set of reference genes (but see Boncristiani et al, 2013) or specific sets of reference genes (Cameron et al, 2013;Reim et al, 2013) in the future. Regardless of the method of quantification, the experimental treatments unambiguously and consistently affected the titer of DWV in the developing bees.…”
Section: Discussionmentioning
confidence: 99%
“…Each biological sample was run in technical triplicate on an ABI Prism 7500 Real-Time PCR system (Applied Biosystems) for measuring candidate gene transcript levels, in comparison with those of the reference gene actin by means of the ΔΔCt method (Livak and Schmittgen, 2001). Studies have shown that actin is stably expressed during honey bee development (Lourenco et al, 2008;Reim et al, 2012) as well as in adults (Cameron et al, 2013). Therefore, actin is commonly used as a reference gene in studies of honey bee gene expression (Scharlaken et al, 2008;de Azevedo and Hartfelder, 2008;Lourenco et al, 2008;Wang et al, 2009).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Each biological sample was run in technical triplicate on an ABI Prism 7500 Real-Time PCR system (Applied Biosystems) for measuring AmILP1 and AmILP2 transcript levels in comparison with those of the reference gene Amrp49 by means of the ΔΔCt method (Livak and Schmittgen, 2001). Studies have shown that Amrp49, which has been renamed as rpl23 (AF441189) in the honey bee genome version Amel 4.5, is stably expressed during larval development (Lourenço et al, 2008;Reim et al, 2013) and in adults (Cameron et al, 2013). Therefore Amrp49 is commonly used as a reference gene during the larval stage (de Azevedo and Hartfelder, 2008;Martins et al, 2010) and also the adult stage of honey bees (Ben-Shahar et al, 2003;Navajas et al, 2008).…”
Section: Real-time Quantitative Pcr Analysesmentioning
confidence: 99%